#TITLE_ALTERNATIVE# - ( NIM 15310016 ), MUCHTAZAR
Diarrhoeal is a kind of water-borne diseases which often occured in Bandung City. In 2012, the total cases of diarrhoeal is 100,583 cases or approximately about 4.12% of total disease cases in Bandung City. The high incidence of diarrhoeal disease probably caused by a shortage of clean and safe water sources for the people which now approximately many of water sources in Bandung City has been contaminated by feces. In this research, the correlation of those factors is measured by chi-square statistical test based on the data which gathered from field survey in six subdistricts of Bandung City. The six subdistricts are Bandung Wetan, Astana Anyar, Sumur Bandung, Coblong, Sukajadi, and Cibeunying Kaler. Based on this research, it is known that the diarrhoeal incidence is assosiated with the type of water sources which used by the people for cleaning food and cooking utensils as well as for washing hands and bathing. The results show that piped water from PDAM has minimum risk for causing diarrhoeal disease while dug well water has maximum risk for causing diarrhoeal in comparison with the other water sources. Besides of that, it is known that the methods of water treatment which used by the people also influence the association. If the people have treated water adequately, there will be no significant risk differences among all of water sources such as for drinking water which the people generally has treated it well before used. Therefore, some of the steps that we can do to minimize diarrhoeal disease incidence in Bandung City are with increasing people access to clean and safe water sources by building better infrastructures for water sources as well as with socializating simple water treatment methods which can be conducted by people before the water was used for any purposes.